The role of pressure in the electrical transport of doped plasticized polyanilines - Fier, I. [UNESP] (2012)
The behaviour of dc longitudinal and transverse conductivity in self-assembled plastdoped films of polyaniline has been studied over the range of 9 K to 320 K, under different applied mechanical pressures. We observe a progressive evolution of the conductivity picture as the applied pressure is increased, especially in the transverse direction, where the conductivity tends to lower as the pressure is increased. (C) 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim